The bronze horseman : Falconet's monument to Peter the Great - Schenker, Alexander M. (Yale University Press, 2003)
This is a comprehensive treatment of the most consequential work of art ever to be executed in Russia - the equestrian monument to Peter the Great. Schenker deals with the cultural setting that prepared the ground for the monument and provides life stories of those who were involved in its creation.